2018
DOI: 10.15390/eb.2018.7220
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Synthesis on Turkish Metaphor Studies of Teachers

Abstract: Bu araştırmada Türkiye'de öğretmen kavramı üzerine yapılan metafor çalışmalarının meta-sentez yöntemiyle değerlendirilmesi amaçlanmıştır.Araştırmada 2004-2016 yılları arasında yayımlanmış olan ve öğretmene ilişkin metaforlara yönelik nitel araştırma yöntemini merkeze alan ya da nitel bulguları olan 11 yüksek lisans tezi ve 32 araştırma makalesi analiz edilmiştir. Çalışmaların seçiminde Google Akademik, YÖK Akademik, YÖK Ulusal Tez Merkezi, TÜBİTAK ULAKBİM, EBSCOhost-ERIC, Web of Science veri tabanlarından fayd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 32 publications
(28 reference statements)
0
7
0
2
Order By: Relevance
“…The overwhelming majority of metaphor-based studies in the field of social studies education are aimed at measuring the perceptions or attitudes of the sample group on a particular subject. For this reason, the adopted methods are qualitatively oriented descriptive analyzes, as stated in other meta-analysis studies, and are generally based on collecting data from sample groups through semi-structured interviews or questionnaire forms (Table 4) (Gezer, 2020;Koca, Kaya, & Gökçimen, 2020;Yıldızlı, Acar Erdol, Baştuğ, & Bayram, 2018). In the typical implementation of this method, a questionnaire form containing only one open-ended question is given to the sample groups and the participants are explicitly asked to compare a concept with another concept and to explain the reason for their analogies.…”
Section: General Results About Studies On Metaphormentioning
confidence: 99%
“…The overwhelming majority of metaphor-based studies in the field of social studies education are aimed at measuring the perceptions or attitudes of the sample group on a particular subject. For this reason, the adopted methods are qualitatively oriented descriptive analyzes, as stated in other meta-analysis studies, and are generally based on collecting data from sample groups through semi-structured interviews or questionnaire forms (Table 4) (Gezer, 2020;Koca, Kaya, & Gökçimen, 2020;Yıldızlı, Acar Erdol, Baştuğ, & Bayram, 2018). In the typical implementation of this method, a questionnaire form containing only one open-ended question is given to the sample groups and the participants are explicitly asked to compare a concept with another concept and to explain the reason for their analogies.…”
Section: General Results About Studies On Metaphormentioning
confidence: 99%
“…For example, in this study, it was determined that teachers mostly produced the "sun" metaphor. Similarly; Yildizli, Erdol, Bastug and Bayram (2018) found in their meta-analysis study on teacher metaphor research in Turkey that the "sun" metaphor is among the metaphors that teachers mostly. Sokmen, Kilic and Yildirim (2020) also found that classroom teachers most often refer to teachers as "the sun".…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, an increase in studies conducted at national level with meta-synthesis method in the field of education has been noticed (e.g. Alkış Küçükaydın, 2019; Ceylan, Uştuk & Çomoğlu, 2017;Çiftçi & Karaman, 2019;Dağhan & Akkoyunlu, 2015;Dede & Arslan, 2019;Öztürk & Güven, 2020;Polat, 2015;Yıldırım, Çalık & Özmen, 2016;Yıldırım, Kurşun & Göktaş, 2015;Yıldızlı, Acar Erdol, Baştuğ & Bayram, 2018;Yildirim, 2016;Yücel-Toy, 2015). With the increase in these studies, by classifying many studies accumulated in different fields of education, comparing and evaluating the focus subjects and the findings obtained, the prominent trends and gaps in these areas have been revealed.…”
Section: Methodsmentioning
confidence: 99%